Influence of process parameters on the microstructure and mechanical properties of friction stir welds of AA2014 and AA6063 aluminium alloys using response surface methodology. (1st February 2022) - Ramamurthy, M; Balasubramanian, P; Senthilkumar, N; Anbuchezhiyan, G
Abstract: Welding dissimilar alloys of aluminium are quite cumbersome due to their lower melting temperatures and difficulty in welding. To resolve this, solid-state procedure friction stir welding (FSW) is utilized largely in industries. In this present research, dissimilar aluminium alloys AA2014 and AA6063 is joined using the FSW procedure to achieve higher yield strength, ultimate tensile strength and microhardness. Experiments were planned as per response surface methodology (RSM) based central composite design (CCD), for four input parameters (tool pin profile, rotational speed, axial force and traverse speed). Micrographs of the weld show grain refinement and proper fusion of materials which increases the mechanical strength and bonding. Outcomes from the experiment show that the considered input parameters significantly influence all the outputs. The optimum condition was evolved from multiobjective optimization procedure using desirability approach (DA) which are 1010 rpm rotating tool speed, 25 mm min −1 as tool traverse speed, 7 kN of axial force with triangular pin profile. The second-order regression model predicts the output responses with lower residuals and the confirmation experiment outputs produces a maximum deviation of 7.94% with investigational outcomes with optimum condition. Micrographs shows that the heat affected zone (HAZ) region is free from voids, oxides, and cracks. The nugget zone has the flow of materials from both the base metals and the flow track is clearly visible.